STUDIES ON THE VOCALISATION OF THE SEA COW DUGONG DUGON IN CAPTIVITY - Nair, R V; Lalmohan, R S (Indian Journal of Fisheries, 2011)
The voice of the sea cow, Dugong dugon, is recorded for the first time,which is a chirp-squeak of frequency 3 kHz. The sound is compared with that ofthe American sea cow. The probable utility of the sound is discussed.